Kebun Gizi dan Isi Piringku Menuju Kemandirian Pangan Desa Karangasem - Dyah Umuhanik; Luthfia Putri Oktaviana; Diyan Muslikha; Ida Priyantiningrum; Zulfa Aulia; Tasya Octaviani; Natzwa Aulia Dwi Trestya; Ersa Novalia Rahmadhani; Abdullah Habib Muhadzdzib; Dzafitri Fadhli Robbi; Abiyyu Syafiq; Naza Yaumis Ziham; Rosida Nur Syamsiyati (CV. ITTC INDONESIA, 2026)
The utilization of home gardens as a source of household food has become increasingly important amid limited agricultural land and rising food prices. This community service program aimed to enhance the utilization of home gardens through the Nutrition Garden (Kebun Gizi) program while improving the understanding of PKK women regarding balanced nutrition through the